Report of a Working Group on Prunus (Second Meeting): Held in Florence, 22-24 October 1985 - International Board for Plant Genetic Resources; United Nations Development Programme (1985)
Report of the ECPGR Prunus Working Group meeting, second meeting, 22-24 October 1985, Florence, Italy